PENERAPAN METODE UTAUT UNTUK MENGUKUR PENERIMAAN, PENGGUNAAN, DAN KEPUASAN MAHASISWA TERHADAP SISTEM INFORMASI AKADEMIK UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA - Irene Cindy Yeanne Vitrin (2021)
The existence of an information system for a university plays a very strategic role in producing quality information. The Academic Information System at UPN "Veteran" Jakarta is a system designed to process academic administration data. The goal is to facilitate the university in obtaining effectiveness and efficiency in data processing. To be able to find out whether a system is running that can be accepted by the user, it is necessary to do a study. One of the determining factors for the success of implementing a system is by testing using the Unified Theory of Acceptance and Use of Technology (UTAUT) model which consists of performance expectancy variables, effort expectancy, social influence, facilitating conditions on behavior intention to use the system. This study distributed questionnaires to 464 students of UPN "Veteran" Jakarta. For data analysis methods using IBM SPSS Amos. The results of hypothesis testing from data processing show that the constructs of performance expectancy, social influence, facilitating conditions on behavior intention to use the system are acceptable. While the effort expectancy on behavior's intention to use the system was rejected, so that overall students were quite satisfied with the SIAKAD UPN "Veteran" Jakarta.